2018
DOI: 10.1016/j.vaccine.2018.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of maternal pertussis vaccination in preventing infection and disease in infants: The NSW Public Health Network case-control study

Abstract: Maternal pertussis vaccination with a 3-component acellular vaccine was found to be highly effective at preventing severe disease in infants, but was less effective at preventing disease which did not require hospitalisation. The overall VE reported in this study was lower than in prior studies and suggests that maternal vaccination, while an effective strategy at preventing severe pertussis, is less effective at protecting against infection or mild disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 25 publications
2
58
1
Order By: Relevance
“…Eight studies fulfilled the inclusion criteria for the assessment of vaccine effectiveness (VE), including four cohort studies [16,[43][44][45] and four case-control-studies [46][47][48][49] (Table 2). The populations of the studies by Amirthalingam et al [43] and Dabrera et al [47] were included in the study by Amirthalingam et al [16] (personal communication, Gavin Dabrera, October 17th, 2018).…”
Section: Vaccine Effectiveness Evidence Base and Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies fulfilled the inclusion criteria for the assessment of vaccine effectiveness (VE), including four cohort studies [16,[43][44][45] and four case-control-studies [46][47][48][49] (Table 2). The populations of the studies by Amirthalingam et al [43] and Dabrera et al [47] were included in the study by Amirthalingam et al [16] (personal communication, Gavin Dabrera, October 17th, 2018).…”
Section: Vaccine Effectiveness Evidence Base and Risk Of Biasmentioning
confidence: 99%
“…Five [16,43,45,47,49] of the eight studies were judged as having a serious RoB, while three studies had a moderate RoB [44,46,48]. The main reasons for these classifications were selection bias, and imprecise outcome definitions.…”
Section: Vaccine Effectiveness Evidence Base and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies indicate that pertussis vaccination in the third trimester reduced infection, hospitalisation, and mortality in infants compared with no vaccination in pregnancy 7475767778. A large British retrospective cohort study using primary care data demonstrated that the benefit of passive maternal immunity did not persist beyond the third dose of primary immunisation in the infant 79.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
“…Maternal immunization during pregnancy, taking advantage of transplacental transfer of pertussis antibodies [1,3,12], was proposed to indirectly protect neonates against pertussis. This strategy achieves high pertussis antibody concentrations in infants [13], and is 64-93% effective in preventing disease among infants aged \ 2 months [14][15][16][17][18][19][20][21]. Moreover, breakthrough disease among infants whose mothers were vaccinated during pregnancy was less severe than those born to unvaccinated mothers [22].…”
Section: Introductionmentioning
confidence: 99%